2022
DOI: 10.3390/min12040409
|View full text |Cite
|
Sign up to set email alerts
|

Field Studies on the Effect of Bioaugmentation with Bacillus amyloliquefaciens FZB42 on Plant Accumulation of Rare Earth Elements and Selected Trace Elements

Abstract: This study is an investigation of the effect of soil bioaugmentation (inoculation) on a field scale with the commercially available product RhizoVital®42, containing Bacillus amyloliquefaciens FZB4, on element bioavailability, plant biomass production, as well as accumulation of rare earth elements (REEs), germanium, and selected trace elements. Zea mays and Helianthus annuus were selected as test plants. Post-harvest, results showed inoculation increased biomass production of Z. mays and H. annuus by 24% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Besides Okoroafor et al [151], after applying B. velezensis FZB42 (formerly B. amyloliquefaciens FZB4) in maize and common sunflower cultivations, detected over 20% increase in biomass production in each of the crops. Moreover, inoculation with the tested preparation increased the bioavailability of soil elements.…”
Section: Promoting Plant Growth By the Bacteria Of The Genus Bacillus...mentioning
confidence: 94%
“…Besides Okoroafor et al [151], after applying B. velezensis FZB42 (formerly B. amyloliquefaciens FZB4) in maize and common sunflower cultivations, detected over 20% increase in biomass production in each of the crops. Moreover, inoculation with the tested preparation increased the bioavailability of soil elements.…”
Section: Promoting Plant Growth By the Bacteria Of The Genus Bacillus...mentioning
confidence: 94%
“…In this study, we found highly competitive capacities between J. curcas and M. esculenta in bioaccumulating more soil PTEs than V. unguiculata plants. This might be driven by a common transport mechanism in taking up soil Cd, Pb and Hg in both plants owing to similarities in both plants' physiology (same family Euphobiaceace) [24,27].…”
Section: Influence Of Soil and Plant Characteristics On Trace Element...mentioning
confidence: 99%